2012
DOI: 10.1097/aln.0b013e31827005e9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Cardiac Arrests in Adults Undergoing Noncardiac Surgery

Abstract: Intraoperative blood loss as indicated by the amount of transfusion was the most important predictor of ICA. The urgency of surgery and the preoperative composite indicators of health such as American Society of Anesthesiologists status and functional status were other important risk factors. The high case fatality suggests that primary prevention might be the key to reducing mortality from ICA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
80
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 29 publications
10
80
0
2
Order By: Relevance
“…Among the reduced morbidities seen with a restricted transfusion strategy were lower rates of re-bleeding, nosocomial infection, multi-organ failure, heart failure, myocardial infarction and mortality rates were reduced by about half [66]. In a recent study, Goswami et al [67] prospectively assessed the incidence, risk factors and survival outcome of intraoperative cardiac arrest in adult patients undergoing non-cardiac surgery utilizing the American College of Surgeons National Surgical database from the years 2005 to 2007 (n = 362,767). Intraoperative cardiac arrest was reported in 262 patients, with death rate of 44% within 24 h and 63% within 30 days.…”
Section: Conservative Blood Transfusionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among the reduced morbidities seen with a restricted transfusion strategy were lower rates of re-bleeding, nosocomial infection, multi-organ failure, heart failure, myocardial infarction and mortality rates were reduced by about half [66]. In a recent study, Goswami et al [67] prospectively assessed the incidence, risk factors and survival outcome of intraoperative cardiac arrest in adult patients undergoing non-cardiac surgery utilizing the American College of Surgeons National Surgical database from the years 2005 to 2007 (n = 362,767). Intraoperative cardiac arrest was reported in 262 patients, with death rate of 44% within 24 h and 63% within 30 days.…”
Section: Conservative Blood Transfusionmentioning
confidence: 94%
“…Intraoperative cardiac arrest was reported in 262 patients, with death rate of 44% within 24 h and 63% within 30 days. Progressive increase in intra-operative cardiac arrest was associated with the amount of RBC transfusion (adjusted odds ratios: 2.51, 7.59, 11.40 and 29.68 for those receiving 1-3, 4-6, 7-9 and ‡10 units, respectively) [67].…”
Section: Conservative Blood Transfusionmentioning
confidence: 99%
“…Cardiac arrest in patients after receiving anesthesia for emergency surgery occurs at a rate of more than twice that of elective surgical cases, and also with significantly higher mortality rates 16. Two studies reported that 50%–60% of all episodes of cardiac arrest in surgical patients occurred in patients undergoing emergency surgeries 2,7.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed many factors, such as age,5,11 underlying conditions,1 American Society of Anesthesiologists (ASA) physical status classification,4,6,10 hemodynamic changes,12 blood loss,6 the anatomic site of the surgery,5,10 and the types and severity of injuries (for example: blunt trauma and vascular injuries)13,14 associated with cardiac arrest during anesthesia. Recognition of such risk factors may help anesthesia care providers to plan appropriate anesthetic care, including the preparation of resuscitation equipment and medications in order to deal promptly with cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
“…3,7---11 These differences in incidence may vary greatly mainly because the studied period varies significantly from 2 to 10 years and there is a lack of adequate epidemiological recording. 12 The importance of the length of the study time is crucial, since improvements in technologies and in clinical practices may have impacted the study period. 13 Also, with the emphasis on patient safety in anesthesia since the early 1980s, and with more concentrated efforts toward patient safety since the 1990s, a reduction of the incidence of perioperative mortality was observed.…”
Section: Introductionmentioning
confidence: 99%